2004
DOI: 10.1128/jcm.42.4.1837-1839.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chryseomonas luteola Identified as the Source of Serious Infections in a Moroccan University Hospital

Abstract: Chryseomonas luteola has only rarely been reported as a human bacterial pathogen. It has been shown that this organism in particular affects patients with health or indwelling disorders. Most reported cases showed septicemia, meningitis, endocarditis, or peritonitis. Two C. luteola infections observed in Morocco are described in the present study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 17 publications
2
47
0
5
Order By: Relevance
“…Chryseomonas luteola is an aerobic, oxidase-negative, Gram-negative rod that produces a yellow pigmented colony (Anon (Pure Air Controls) 2004a). It is widely distributed in both nature and in hospital environments and is associated with nosocomial infections in humans (Anon (Pure Air Controls) 2004a; Chihab et al 2004).…”
Section: Pcr Detection Limitmentioning
confidence: 99%
“…Chryseomonas luteola is an aerobic, oxidase-negative, Gram-negative rod that produces a yellow pigmented colony (Anon (Pure Air Controls) 2004a). It is widely distributed in both nature and in hospital environments and is associated with nosocomial infections in humans (Anon (Pure Air Controls) 2004a; Chihab et al 2004).…”
Section: Pcr Detection Limitmentioning
confidence: 99%
“…It is a rare cause of pathogenic human infection and has been reported to cause septicemia, endocarditis, and peritonitis among immunocompromised individuals or individuals with indwelling devices. 3,4 While P. aeruginosa causes a devastating form of endophthalmitis, P. luteola is associated with a more indolent course. P. luteola endophthalmitis was characterized by gradually worsening hypopyon, vitritis, IOP elevation, and light-colored deposits capsular deposits similar to Pseudomonas oryzihabitans infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, P. luteola isolates were highly resistant to colistin in vitro, and empirical colistin treatment failed in 1 patient. It was reported that monotherapy was sufficient in most cases (5,9,17,20). We believe that carbapenems might be suitable for hospital-acquired P. luteola infections, as all of the isolates studied were susceptible to imipenem.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Tanzania that investigated extended spectrum beta-lactamases among gram-negative bacteria of nosocomial origin, P. luteola was reported as a nosocomial pathogen in 1 patient in an intensive care unit of a tertiary hospital (4). In this study, we reviewed all cases of infection related to P. luteola from 1988 to date (Table 4) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Of the reported cases of P. luteola, bacteremia was the most common infection.…”
Section: Discussionmentioning
confidence: 99%